Effect of genetic and non-genetic factors on morphometric traits of indigenous cattle breeds used for sporting event in Tamil Nadu - PRIYADHARSINI, R; GOPINATHAN, A; KARTHICKEYAN, S M K; JAGATHEESAN, P N RICHARD (The Indian Journal of Animal Sciences, 2021)
A total of 310 sporting bulls belonging to Pulikulam, Kangayam, Umblachery and non-descript cattle were used to assess the morphometric traits such as body weight (kg) and body length (cm), height at withers and chest girth (cm), face length and face width (cm), horn length and horn circumference and skin thickness (mm). The body measurements were analyzed to study the effect of different factors such as place of event, genetic and age groups by the general linear model. From this analyses, body weight and chest girth did not vary among different genetic groups, but, numerically higher body weight values were observed at more than six years of age. Kangayam bulls had significantly higher height at withers, when compared to other genetic groups. Pulikulam breed had higher face length (46.79±1.52 cm), maximum horn length (31.38±3.05 cm) and face width (20.53±1.04 cm), when compared to other genetic groups. Age of the bull, genetic groups and place of event did not show any significant effect on skin thickness. Overall, Pulikulam breed had optimum parameters with respect to body length, body weight, horn length and horn circumference and these attributes would confer jallikattu breed when compared to other recognized breeds.